O que são leis da natureza segundo D. M. Armstrong - Dalmolin, Mariana Battistini (2015)
This work is a study on the theory of laws of nature proposed by the Australian philosopher D. M. Armstrong in his work What is a Law of Nature?, published in 1983. In that text, Armstrong shows the insufficiency of the regularty theory and, then, proceeds to develop his own theory, which is able to answer to several of the regularity theory's outstanding issues. In the first chapter of this work, we present (1.1) the naive regularity theory, as well as the critiques that it received from Armstrong and other authors. Afterwards (1.2), we present three suggestions to sophisticate that theory, which are not successful to address the difficulties found in its naive version. Therefore, the regularity theory is refuted, and a new theory of laws is needed. In the second chapter, we present, firstly (2.1), an assumption of Armstrong's theory of laws his realism about universals , and we see how it can be applied to a theory of laws. Afterwards (2.2), we present Armstrong's fundamental thesis: a law is a relation between universals and simultaneously an universal in itself, which regulates the behavior of particulars and generates uniformities in nature in virtue of the instaniation relation. We also show (2.3) how such theory makes it possible to deal with the difficulties faced by the regularity theory. In the third chapter, we evaluate the role of the concept of necessity in Armstrong's theory. Firstly (3.1), we deepen our understanding of the necessitation relation N, and, afterwards (3.2), we show that Armstrong rejects the thesis according to which laws are metaphisically necessary and advocates for their contingency. Therefore, the understanding of his theory is centered in the distinction between the nomic necessity asserted in his conception of laws, on one hand, and the metaphysic necessity of laws, which Armstrong denies, on the other